NUGGET IKAN KEMBUNG DAN DAUN KELOR SEBAGAI MAKANAN SELINGAN TINGGI PROTEIN UNTUK ANAK SEKOLAH DASAR - Prasasti, Tresna Dewi; Pusparini, Pusparini; Rosmana, Dadang; Sulaeman, Agus (Jurnal Gizi dan Dietetik, 2024)
One of the nutritional problems commonly found in school-aged children is stunting. According to the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting is 21.6%, down 2.8% from 2021. The development of nugget products can be used as an alternative high-protein snack as an effort to prevent and overcome stunting. This research aims to determine the formulation of nuggets based on mackerel and moringa leaves regarding the organoleptic properties and protein content of the best product formulation. The research method uses an experimental design with a completely randomized design. The nugget formulation was obtained from the calculation results, the formulation for mackerel and moringa leaves, F1 (90%:10%), F2 (85:15%), F3 (80%:20%). Hedonic tests were carried out to determine the organoleptic properties of nugget products and protein content tests to determine protein levels using the Kjeldahl micro method. The results of the research show that there is a significant difference, namely in the taste aspect. Then overall the superior product is formula three. The protein content of the three per serving formula is 10.8 grams, meeting the protein adequacy of 235%. Formula three nugget products can be used as an alternative snack to prevent stunting. Further research by giving this product to elementary school children.